ENGLISH TEACHERS AND STUDENTS READINIESS IN UTILIZING MALL IN ENGLISH DISTANCE LEARNING CONTEXT - Pande Putu Justiana; Made Hery Santosa; Gede Mahendrayana (Eltin Journal : Journal of English Language Teaching in Indonesia, 2022)
This current study aims to identify teachers’ and students’ readiness in utilizing MALL during distance teaching and to investigate factors affect the readiness in using MALL in the context of online teaching.  In conducting the study, a mix method with a survey was conducted. The data were collected through questionnaire and interview. This study involved the English teachers and students in SMA Negeri 1 Mengwi. The result of data analysis found that teachers are ready but requires some improvement to use MALL in the context of online teaching. It can be seen from the overall mean score of teachers’ readiness (3.91) (Technology=4.50, Ability to Adapt=4.06 Openness=4.06, People=3.81, Budget=3.50, and Believe=3.25). Meanwhile, the students were categorized as not ready with 3.25 mean score. Mean score from all indicators are also lower than teacher (Technology=3.57, Ability to Adapt=3.45 Openness=3.45, People=3.16, Budget=2.87, and Believe=3.03). There are several factors that support the readiness of teachers and students in implementing MALL. Mainly in terms of technology and budget readiness.